Changes To The Layout Of 36 M2 Type Residential Houses Along Jl. Karya 1 In The Uir Campus Area Associated With Commercial Activities - andrie Herdiansyah; Apriliana Hidayati Nurdin; Mutiara Yaumil Atika (Talenta Publisher, 2026)
Increasing population density, the need for housing is also increasing, especially in the city of Pekanbaru. To meet the need for adequate housing, the Government together with the private sector build housing for various levels of society in the form of real estate and Perumnas which is equipped with various facilities. One of the factors contributing to the creation of comfortable living is the presence of commercial facilities around residential areas, which play a role in providing supporting activities while strengthening the socio-economic connection between residents and their environment. This research was conducted along Jalan Karya I, an area within the scope of the Islamic University of Riau (UIR) campus. The approach used is descriptive with a qualitative-rationalistic analysis framework, so that the data obtained are not only processed in the form of tables or visual illustrations, but also interpreted through logical and argumentative considerations. The purpose of this study is to determine the influence of house layout with a commercial approach. The research variables are divided into physical and non-physical aspects; Physical aspects include the visual representation of the building mass, including its configuration and spatial layout, while non-physical aspects include regulatory provisions governing building construction and the socio-economic dynamics of the area's residents. The research findings are that there is motivation for homeowners to change their homes from residential to commercial because of the relationship between economic activities towards change, where the potential for campus literacy is an influence